2020
DOI: 10.3389/fphar.2020.559593
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Platelet Count with Inflammation and Response to Anti-TNF-α Therapy in Patients with Ankylosing Spondylitis

Abstract: Background: Increased platelet count has been reported in ankylosing spondylitis (AS) patients, but its clinical significance is still largely elusive. The objective of this study was to evaluate the clinical role of platelet count in AS patients, especially its impact on treatment outcomes. Methods: A case-control study containing 35 AS patients receiving anti-tumor necrosis factor-α (anti-TNF-α) therapy and 45 healthy controls was performed, and AS patients were followed at least 6 months after anti-TNF-α th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 72 publications
2
13
0
1
Order By: Relevance
“…In another study in ankylosing spondylitis, platelet count was correlated with disease activity, and anti-TNF treatment decreased the platelet count. In regression analysis, a high platelet count may predict a poorer response to anti-TNF-α therapy [24]. Similar to our results, in the last study conducted in 2020, NLR, PLR, MPV and CRP decreased after the biological treatment, including infliximab, etanercept, adalimumab and ustekinumab, and this result was independent of drug [8]…”
Section: Original Articlesupporting
confidence: 88%
“…In another study in ankylosing spondylitis, platelet count was correlated with disease activity, and anti-TNF treatment decreased the platelet count. In regression analysis, a high platelet count may predict a poorer response to anti-TNF-α therapy [24]. Similar to our results, in the last study conducted in 2020, NLR, PLR, MPV and CRP decreased after the biological treatment, including infliximab, etanercept, adalimumab and ustekinumab, and this result was independent of drug [8]…”
Section: Original Articlesupporting
confidence: 88%
“…In particular, TNFa is a pleiotropic cytokine that is involved in atherothrombosis in several pathways: TNF-a increases the expression of adhesion molecules by endothelium and as well enhances leukocyte adhesion and rolling (46), and it is involved in the implementation of endothelial dysfunction via increase of reactive oxygen species production and impairment of NO-mediated vasodilation (47)(48)(49)(50). Finally, there is evidence of increased platelet aggregation upon TNF-a stimulation (51)(52)(53)(54). MIP-1b was shown to be released by macrophages and smooth muscle cells in atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they are also important mediators of inflammatory response. Studies have shown that the peripheral blood PLT count in patients with AS is higher than that in healthy individuals 29,30 . Although the specific mechanisms involving PLTs in the pathogenesis of AS are not clear, it has been reported that activation of PLTs by thrombin, histamine, tumor necrosis factor‐α, and interleukin (IL)‐12 leads to adhesion between activated PLTs and neutrophils, monocytes, eosinophils, and T lymphocyte subsets, which may be a key factor in the activation of inflammatory pathways 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the peripheral blood PLT count in patients with AS is higher than that in healthy individuals. 29,30 Although the specific mechanisms involving PLTs in the pathogenesis of AS are not clear, it has been reported that activation of PLTs by thrombin, histamine, tumor necrosis factorα, and interleukin (IL)-12 leads to adhesion between activated PLTs and neutrophils, monocytes, eosinophils, and T lymphocyte subsets, which may be a key factor in the activation of inflammatory pathways. 31 Furthermore, platelet factor 4 (chemokine [C-X-C motif] ligand 4) is the most abundant protein in the alpha granules of PLTs, and the first member of the chemokine family to be recognized in PLTs.…”
Section: Ta B L E 3 Correlations Of Sii With Crp Esr and Basdai In As Patientsmentioning
confidence: 99%